GEOMETRY EXPLORATION ACTIVITIES ASSISTED WITH DYNAMIC GEOMETRY SOFTWARE (DGS) IN A TEACHER EDUCATION CLASSROOM - Samsul Maarif; Wahyudin Wahyudin; Muchamad Subali Noto; Wahyu Hidayat; Herri Mulyono (IKIP Siliwangi and I-MES, 2018)
The aims of this study were conducted to investigate the effectiveness of pre-service teachers’ geometric exploration activities assisted by Dynamic Geometry Software (DGS) Cabri II Plus computer application in constructing geometry proofs in a teacher education classroom. To these ends, mix-method design. A total of 72 pre-service teachers taking geometry course participated in the study. Findings of the study show that students who participated in geometric exploration activities assisted by DGS Cabri II Plus computer application had better achievement compared to their counterpart. The use of DGS Cabri II Plus computer application was observed to enable the students to present diagrams of verification problems appropriately, determine the valid conjectures, and make justification regarding the statements in the written proof. More importantly, participating in geometric exploration activities assisted by DGS Cabri II Plus computer application provide students with opportunities to explore alternative proofs related to geometry.